2015
DOI: 10.1016/j.medici.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Short-term results of quality of life for curatively treated colorectal cancer patients in Lithuania

Abstract: The present study showed that majority of functional scale scores came back to the preoperative level during the first 3 months after colorectal cancer surgery. Differences in QoL according to surgical approach are mostly expressed on this period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
3
6
0
2
Order By: Relevance
“…HRQoL among our patients was good with respect to the global health status and overall quality of life (GHS/QOL) with an overall mean score of 80.56. This is comparable with the previous study by Lizdenis et al, 19 in which the reported mean score for global quality of life was reported to be 72.27 at 3 months post-surgery.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…HRQoL among our patients was good with respect to the global health status and overall quality of life (GHS/QOL) with an overall mean score of 80.56. This is comparable with the previous study by Lizdenis et al, 19 in which the reported mean score for global quality of life was reported to be 72.27 at 3 months post-surgery.…”
Section: Discussionsupporting
confidence: 91%
“…Apart from that, our patients reported relatively high scores (more than 80) for functionalities that include emotional functioning (tension/worry/irritability/depression), role functioning (limited in work or leisure), cognitive functioning (concentration/memory trouble) for QLQ-C30 which is similar to reference study Lizdenis et al 19 This could be explained by the better management of CRC patients at our centre that involves multidisciplinary approach such as oncologists, colorectal surgeons, pain management team and palliative physicians. Sexual functioning is one of the most common long-term effects of cancer treatment and is an essential component of quality of life that should be addressed adequately.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is worth noting that, after receiving the mobile web-based educational intervention, the treatment group experienced a positive effect on their quality of life within a short period after hospital treatment. This is further supported by the fact that some patients had a marked improvement in their quality of life within the first month, indicating the necessity of measuring patients’ quality of life during the early post-surgery stages [33]. The quality of recovery scores dropped on postoperative days 1 and 3 but markedly improved from day 6 onward and returned to preoperative levels a month after surgery [34].…”
Section: Discussionmentioning
confidence: 99%
“…As pesquisas indicam que em pacientes com câncer gástrico, câncer colorretal e câncer de pâncreas, a QV retorna a níveis de base aferidos antes dos procedimentos cirúrgicos (Amemiya et al, 2007;Munene et al, 2012;Eshuis et al, 2015;Lizdenis et al, 2015).…”
Section: Características Gerais Da Amostraunclassified